2007
DOI: 10.1097/01.tp.0000295931.39616.25
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Risk Assessment of Accidental ABO-Incompatible Thoracic Organ Transplantation Before and After 2003

Abstract: The observed and predicted likelihoods of accidental incompatible thoracic organ transplantation are comparable. These likelihoods are several orders of magnitude smaller than other hazards associated with solid organ transplantation. The PRA model indicates that changes that followed the March 2003 accident further reduced the likelihood of accidental incompatible implantation by roughly two orders of magnitude. Quantitative estimates from PRA can be used to assess risks in healthcare and to gauge the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…One way of dealing with this challenge is to simply limit the application of HRA techniques to those clinical processes or tasks, which do not fall into this category. For example, Cook and colleagues performed a PSA to quantitatively assess the likelihood of unintentional ABO-incompatible (wrong blood type) thoracic organ transplant [79]. The blood type matching process is complicated, but a national standard exists.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…One way of dealing with this challenge is to simply limit the application of HRA techniques to those clinical processes or tasks, which do not fall into this category. For example, Cook and colleagues performed a PSA to quantitatively assess the likelihood of unintentional ABO-incompatible (wrong blood type) thoracic organ transplant [79]. The blood type matching process is complicated, but a national standard exists.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, there has been limited research examining the range of patient safety vulnerabilities that occur in transplantation. While safety events such as ABO-incompatible organ transplantation,[72] infection,[73] organ rejection, and complications after surgery[74] have been reported, a systematic review of the literature on patient safety in transplantation found that the majority of articles are based on expert opinions, not data. [75*] The relative lack of empirical patient safety data for the multidisciplinary and complex field of surgery stands in stark contrast to other high risk industries such as air and land transportation, where safety vulnerability assessments are routinely performed, analyzed, and lead to continuous process improvement.…”
Section: Patient Safetymentioning
confidence: 99%
“…The identified faults are arranged in a hierarchy to demonstrate their interaction and identify areas of vulnerability. In an effort to further understand various healthcare processes, researchers have used FTA along with other PRA methodology tools to evaluate a range of medical errors and adverse events (10–12). …”
Section: Methodsmentioning
confidence: 99%